2012
DOI: 10.1017/s175173111100156x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of release rate of the SF6 tracer on methane emission estimates based on ruminal and breath gas samples

Abstract: The release rate (RR) of sulphur hexafluoride (SF 6 ) gas from permeation tube in the rumen appears to be positively related with methane (CH 4 ) emissions calculated using the SF 6 tracer technique. Gas samples of breath and ruminal headspace were collected simultaneously in order to evaluate the hypothesis that transactions of SF 6 in the rumen are the source for this relationship. Six non-lactating dairy cows fitted with rumen cannulae were subdivided into two groups and randomly assigned to a two-period cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Comparison of breath versus rumen headspace gas sampling for estimation of rumen methane production when using the SF 6 technique has not often been performed. In one such comparison, Martin et al (2010) reported similar methane-emission rates between the 2 methods. The effect of cannula leakage on the accuracy of methane emission measurement has not been thoroughly investigated.…”
Section: Resultsmentioning
confidence: 89%
“…Comparison of breath versus rumen headspace gas sampling for estimation of rumen methane production when using the SF 6 technique has not often been performed. In one such comparison, Martin et al (2010) reported similar methane-emission rates between the 2 methods. The effect of cannula leakage on the accuracy of methane emission measurement has not been thoroughly investigated.…”
Section: Resultsmentioning
confidence: 89%
“…Like NH 3 , TMA diffuses through the rumen wall into plasma and blood stream (Bain et al, 2005). In the liver, the NH 3 is converted to urea as a detoxification mechanism (Meijer et al, 1990;Walt, 1993). Similarly, TMA acts detrimentally (Guest and Varma, 1992;Rappert and Müller, 2005) while liver cells are capable of enzymatically oxidising TMA to TMAO (Baker and Chaykin, 1962;Baker et al, 1963;Gut and Conney, 1993;Bennett et al, 2013).…”
Section: The Fate Of Tma In Ruminantsmentioning
confidence: 99%
“…The correlation between emission values obtained from individual animals and repeatability in the estimated rates was also low for the SF 6 method (Clark, 2010;Pinares-Patiño et al, 2010). Various factors, including permeation rate (Pinares-Patiño and Clark, 2008;Martin et al, 2010b), retention of the tracer in the digestive tract (Lassey et al, 2011), and different behaviour of tracer vs tracee gases (Pinares-Patiño et al, 2010) may affect CH 4 emission measurements with the SF 6 technique. In vitro gas production systems have been modified to measure CH 4 (Pellikaan et al, 2011a;Navarro-Villa et al, 2011), but they suffer from the same disadvantages as all in vitro techniques (see previous discussion).…”
Section: Mitigation Practicesmentioning
confidence: 99%